Funky grooves: declarative programming of full-fledged musical applications - Nilsson, Henrik; Chupin, Guerric (Springer Verlag, 2016)
There are many systems and languages for music that essentially are declarative, often following the synchronous dataflow paradigm. As these tools, however, are mainly aimed at artists, their application focus tends to be narrow and their usefulness as general purpose tools for developing musical applications limited, at least if one desires to stay declarative. This paper demonstrates that Functional Reactive Programming (FRP) in combination with Reactive Values and Relations (RVR) is one way of addressing this gap. The former, in the synchronous dataflow tradition, aligns with the temporal and declarative nature of music, while the latter allows declarative interfacing with external components as needed for full-fledged musical applications. The paper is a case study around the development of an interactive cellular automaton for composing groove-based music.